Literature and Emigration: Overcoming the Tragedy of Exile - Dzyk, Roman (NGO “German-Ukrainian Dialogue” (Augsburg, Germany), 2023)
The cultural landscape of the twentieth century and, as we have already seen, of the first quarter of the twenty-first century is largely shaped by the factor of emigration. Of course, emigration was not a product of the last century only, but it was during this period that it reached an unprecedented scale for various reasons.
Keywords: Literature; Emigration; Exile; Tragedy of Exile